2007
DOI: 10.1002/jrs.1838
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Raman spectroscopic characterisation of hydrotalcite with CO32− and (MoO4)2− anions in the interlayer

Abstract: Raman spectroscopy has been used to characterise synthetic mixed carbonate and molybdate hydrotalcites of formula Mg 6 Al 2 (OH) 16 ((CO 3 ) 2− ,(MoO 4 ) 2− )·4H 2 O. The spectra have been used to assess the molecular assembly of the cations and anions in the hydrotalcite structure. The spectra may be conveniently subdivided into spectral features on the basis of the carbonate anion, the molybdate anion, the hydroxyl units and water units. Bands are assigned to the hydroxyl stretching vibrations of water. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…The two latter bands were attributed to anti-symmetric and symmetric stretching vibrations of Mo-O bonds, while the other bands are probably attributed to carbonate anions. 23 In general, the spectrum was virtually identical to the spectrum obtained after intercalation of molybdate ions into Al:Zn and Mg:Zn layered double hydroxides. [24][25][26] The Raman spectra clearly showed that the position of the bands changed after the ion exchange reaction.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The two latter bands were attributed to anti-symmetric and symmetric stretching vibrations of Mo-O bonds, while the other bands are probably attributed to carbonate anions. 23 In general, the spectrum was virtually identical to the spectrum obtained after intercalation of molybdate ions into Al:Zn and Mg:Zn layered double hydroxides. [24][25][26] The Raman spectra clearly showed that the position of the bands changed after the ion exchange reaction.…”
Section: Resultssupporting
confidence: 55%
“…The band at 318 cm -1 was assigned to the ν 4 bending mode of the molybdate anions, and the other bands were related to the NZHA structure. [23][24][25] The TGA/DTA analyses of the compounds (Figure 4) revealed three mass loss events for NZHA (Figure 4a) with minima at 90, 270, and 326 °C in the DTA curves.…”
Section: Resultsmentioning
confidence: 99%
“…The minor peaks at $157 and 1064 cm À1 (solid arrows) can be assigned to the external vibration of the carbonate CO 3 group [42] and the m 1 symmetric C-O stretching mode of CO 3 2À [46][47][48], respectively. Other minor peaks at $233 and 560 cm À1 can be ascribed to the vibration of chlorine Cl 1 ; the A 1g breathing mode of Mg-Cl octahedral in MgCl 2 at 233 cm À1 [49][50][51] and Cl 2 signal at 560 cm À1 [52].…”
Section: Ft-ir and Raman Analysis Of Powdermentioning
confidence: 99%
“…These bands are attributed to the O-H stretching vibrations of the OH units of -AlOH and -MgOH. [9] Shifts in these bands for the different hydrotalcites are due to slightly different bonding of the hydroxyl groups in each of the hydrotalcite structures synthesised. Bands between 2930 and 3100 cm −1 are due to strongly hydrogen-bonded water molecules to interlayer anions such as arsenate, vanadate or carbonate.…”
Section: Raman Spectra Of Hydrotalcites Synthesisedmentioning
confidence: 99%